Assessment of Urban ASHA workers: Unveiling Urban Dynamics - Jain, Seema; Saxena, Siddharth; Bano, Tanveer; Mittal, Chhaya (Indian Journal of Community Health, 2024)
Background: The World Health Report highlighted the critical role of human resources in health systems, especially noting the human resource crisis in low-income countries due to various challenges such as migration and illness of health workers. The study aims to assess the performance of urban ASHA workers in Meerut and identify factors affecting their performance. Specific objectives include evaluating the delivery of essential services by ASHA workers and understanding the various individual, occupational, and environmental factors that influence their effectiveness. Methodology: The study was conducted with 40 ASHAs from the urban areas of Meerut. Data was collected through interviews using pretested schedules and performance assessments based on structured scales. Beneficiaries were also interviewed to gauge service delivery effectiveness. Chi-square and Fisher exact tests were used to analyze data and understand the association between various factors and ASHA performance. Results & Conclusion: The results were categorized into performance grades based on the ASHAs' scores, showing a distribution among different performance levels. Factors such as age, education, training frequency, occupation, and timely receipt of incentives were found to significantly affect the performance of ASHA workers. The study revealed that younger, better-educated, and regularly trained ASHAs with timely incentives showed better performance.